Edukasi dan Implementasi Korset Gerakan Janin untuk Peningkatan Kesehatan Janin di Komunitas - Nur Hidayah; Munaaya Fitriyya; Ipin Prasojo; Anis Prabowo; Itsna Rachmawati Dewi; Hanifah Azzahra; Amelia Putri Astuti; Diana Mailikhah; Muhammad Asad Prabowo; Graicella Desty Puspitasari1 (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The lack of knowledge among pregnant mothers and posyandu cadres about early detection of fetal complications, especially through monitoring fetal movements, is a major issue driving this community service activity. The high perinatal mortality rate in Sukoharjo, which reached 46 cases in 2024, highlights the urgency of this problem. The aim of this activity is to increase the knowledge of pregnant mothers and cadres about fetal health monitoring and to create the GERNIN Corset (Fetal Movement Movement), a self-monitoring tool for tracking fetal movements. The expected outcomes include improved skills, journal publications, educational videos, and the availability of the GERNIN Corset and posters at posyandu. Implementation methods include socialization, training, application of the GERNIN Corset technology, as well as ongoing assistance and evaluation. This activity successfully significantly increased participants' knowledge. Post-test results showed that 94.37% of participants achieved high scores, up from 67.61% in the pre-test. In conclusion, the methods applied, including the use of the GERNIN Corset, are very effective and have successfully improved the knowledge, attitudes, and skills of pregnant women and health cadres, making it an important step in efforts to reduce child mortality.